2006
DOI: 10.1017/s0021859606006150
|View full text |Cite
|
Sign up to set email alerts
|

Trends in performance of Turkish durum wheats derived from the International Maize and Wheat Improvement Center in an irrigated West Asian and North African environment

Abstract: Turkey is one of the most important durum wheat (T. turgidum L. var. durum Desf.) producers in West Asia and North Africa (WANA). There appears to have been a lack of progress in wheat yields in WANA over recent decades. Most of the modern cultivars grown in WANA are related to crosses produced by the International Maize and Wheat Improvement Center (CIMMYT). During 1999 and 2000, a chronological set of 11 cultivars related to CIMMYT crosses was evaluated using two irrigation regimes near Şanlıurfa, Turkey.Ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
5
2
Order By: Relevance
“…In contrast to studies on winter wheat (Barutçular et al, 2006;Peltonen-Sainio et al, 2009a;Graybosch and Peterson, 2010) and many other studies on spring wheat (Fischer and Edmeades, 2010;Matus et al, 2012;Beche et al, 2014;Maureen, 2019), where from the beginning of the twenty-first century, yield gain has either started to slow down or even plateaued, we found a strong linear increase in wheat yield since 1905 with no indication of yield saturation (Figures 4D, 5A,B). An absolute genetic gain of 24.27 kg ha −1 y −1 with a relative value of around 0.544% per year in a century-long period is equal or better than many other breeding programs in the world (Fischer and Edmeades, 2010;Sadras and Lawson, 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to studies on winter wheat (Barutçular et al, 2006;Peltonen-Sainio et al, 2009a;Graybosch and Peterson, 2010) and many other studies on spring wheat (Fischer and Edmeades, 2010;Matus et al, 2012;Beche et al, 2014;Maureen, 2019), where from the beginning of the twenty-first century, yield gain has either started to slow down or even plateaued, we found a strong linear increase in wheat yield since 1905 with no indication of yield saturation (Figures 4D, 5A,B). An absolute genetic gain of 24.27 kg ha −1 y −1 with a relative value of around 0.544% per year in a century-long period is equal or better than many other breeding programs in the world (Fischer and Edmeades, 2010;Sadras and Lawson, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…However, century-long analysis highly subdued the gain (Cox et al, 1988 ; Austin et al, 1989 ; Berzonsky and Lafever, 1993 ; Donmez et al, 2001 ). Since the beginning of the twenty-first century, progress in increasing the potential yield began to slow down in winter wheat or even reached to plateau in some of the countries (Barutçular et al, 2006 ; Peltonen-Sainio et al, 2009a ; Graybosch and Peterson, 2010 ) and therefore, increased world wheat demand is most likely to be met by the South and East Asian countries including India. Periodic evaluation of released cultivars for associated changes in physiological and agronomic traits can provide the much-needed cue for future breeding strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to studies on winter wheat [31][32][33] and many other studies on spring wheat [6][7][8][9] , where from beginning of 21 st century, yield gain have either started to slow down or even plateaued, we found strong linear increase in wheat yield since 1905 with no indication of yield saturation (Fig. 4d, 5a and 5b).…”
Section: Discussioncontrasting
confidence: 99%
“…However, in century-long analysis, the gains were highly tapered [27][28][29][30] . Since the beginning of the 21 st century, yield potential progress began to slow down in winter wheat or even reached to plateau in some of the countries [31][32][33] and therefore increased world wheat demand is the most likely to be met by South and East Asian countries including India. A number of these studies have established a fact that the periodic evaluation of released cultivars for associated changes in physiological and agronomic traits, which can thus provide the much-needed cue for future breeding strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Yavaros). Instead, testing at four irrigated environments of 11 CIMMYT durum wheat cultivars released in Turkey from 1975 to 2000 revealed an annual rate of GG for GY equal to 0.76% [4], while field trials of twenty-nine durum cultivars released in Morocco between 1949 and 2016 at six sites revealed annual GG for GY of 0.43%, mostly associated with selection for early flowering and higher harvest index [5]. A GG study conducted by De Vita et al [6] at one site, over two seasons, and three agronomic treatments revealed an annual yield gain of 19.9 kg•ha −1 (calculated at 0.36%) when comparing 18 Italian durum cultivars.…”
Section: Introductionmentioning
confidence: 97%